Graffiti U [compact disc] - Urban, Keith, 1967-; Urban, Keith, 1967- (Hit Red Records / Capitol Records Nashville, 2018)
Keith Urban's eighth studio record features first singles Female and Parallel Line as well as the current single Coming Home. He describes the album title as meaning 'pure artistic expression' to him in the sense that there are no parameters.